Menumbuhkembangkan Keterampilan Proses Sains Peserta Didik dan Meningkatkan Kompetensi Guru Melalui Pelatihan Penggunaan Alat Ukur Dasar - Triwiyono Triwiyono; Jan Pieter (Bakti Hayati: Jurnal Pengabdian Indonesia, 2026)
This community service activity aims to develop students' science process skills and improve teachers' competencies through training in the use of basic measuring instruments. The background to this activity is low science process skills and limited learning resources at partner schools. Training is carried out in the preparation, implementation and evaluation stages. Twenty-eight participants, 23 students and five teachers, attended YPPK Teruna Bakti High School in Jayapura City. The training covered measurement concepts and the practical use of measuring instruments such as calipers and micrometers. The results of the activity showed an increase in participants' knowledge and skills in using measuring instruments. This was supported by the evaluation results, which showed a very positive response: 89% of participants strongly agreed that the material improved their knowledge, 96% strongly agreed that the activity improved their knowledge, and 100% strongly agreed that the training improved their skills in using measuring instruments.